1992
DOI: 10.1207/s15327752jpa5901_13
|View full text |Cite
|
Sign up to set email alerts
|

The Ego Impairment Index and Schizophrenia: A Validation Study

Abstract: This study is an extension of our work on a new scale, the Ego Impairment Index (EII; Perry & Viglione, 1991). The index is theoretically based on Beres's (1956) model of ego assessment and was empirically developed on a sample of melancholic, depressed outpatients, diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders (3rd ed. [DSM-III]; American Psychiatric Association, 1980). The EII is derived from the Rorschach Inkblot Test and offers a single composite score of ego impairment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 11 publications
0
70
0
2
Order By: Relevance
“…13,24,31 The second measure was a weighted scaling of strained and disordered cognitive reasoning and is indicative of thought disorder (W SUM 6). 13,24,31 This score is given for responses that involve implausible relationships, autistic logic, and disorganized thought and language. Schizophrenic patients give approximately twice as many of these responses as any other clinical group.…”
Section: Rorschach Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…13,24,31 The second measure was a weighted scaling of strained and disordered cognitive reasoning and is indicative of thought disorder (W SUM 6). 13,24,31 This score is given for responses that involve implausible relationships, autistic logic, and disorganized thought and language. Schizophrenic patients give approximately twice as many of these responses as any other clinical group.…”
Section: Rorschach Measurementmentioning
confidence: 99%
“…Expression of these contents, ie, blood, fire, sex, explosion, anatomy, aggression, morbid, food, and x-ray, is highly elevated among clinical groups including schizophrenic patients. 13,24,31 These 3 variables were summed across all responses and then divided by the total number of responses to all 10 Rorschach stimuli.…”
Section: Rorschach Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Seltzer et al [32] reported that the paranoid schizophrenia group had a signifi cantly better verbal IQ, executive functioning on the Wisconsin Card Sorting Test, and memory for spoken language on the Sentence Repetition Test compared to those of undifferentiated schizophrenia. Auslander et al [33] discriminated nonparanoid schizophrenia from paranoid schizophrenia patients such that nonparanoid patients displayed significantly greater impairment on the Rorschach-Derived Ego Impairment Index compared to their paranoid counterparts, that supported the result of a similar study by Perry et al [34] . The latter studies offer support for the presence of greater ego impairment in nonparanoid schizophrenia than in paranoid schizophrenia.…”
Section: Discussionmentioning
confidence: 56%
“…It consists of three cards; each one has a symmetrical and different inkblot. The task of responding to ambiguous stimuli encourages the respondents to use cognitive aspects such as attention, memory, perception, logical analysis, and underlying psychological processes such as feelings, concerns, experiences, and fantasies, which increase the value of this instrument for the evaluation of self-perception and interpersonal relationships (Perry, Viglione, & Braff, 1992).…”
Section: Instrumentsmentioning
confidence: 99%